Multidrug-resistant Enterobacteriaceae that produce antimicrobial resistance genes isolated from hospital effluents in Peru - Elías Solís, Gladys Estheysi (2025)
Antimicrobial resistance is one of the greatest threats to public health, and hospital wastewater effluents are an important source of transmission for resistant pathogens. The objective of this study was to determine the presence of multidrug-resistant bacteria producing extended-spectrum beta-lactamases, AmpC, and carbapenemases in hospital effluents from three regions of Peru. Bacteria were collected and characterized from nine hospitals using chromogenic media and an automated microbiology system. Conventional PCR was also used to identify resistance genes for beta-lactamases, such as blaCTX-M, blaTEM, blaSHV, blaAmpC, and carbapenemases like KPC, NDM, and IMP. Fifty-five isolates were identified from various healthcare centers, with extended-spectrum beta-lactamase genes, such as blaTEM, found. In level II2 hospitals, the KPC resistance gene was found, particularly in the Regional Hospital of Cajamarca (7%) and the Ate Vitarte Emergency Hospital (13%). Additionally, Salmonella enterica and Stenotrophomonas maltophilia showed resistance to all classes of antibiotics. These findings highlight changes in the epidemiological behavior of bacterial genetic resistance, emphasizing the need to improve hospital wastewater treatment systems and strengthen epidemiological surveillance.